What opportunities do the New EU international investment agreements offer for developing countries? - Axel Berger; Julia Harten (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The issue of how foreign direct investment (FDI) can contribute to sustainable development processes is becoming increasingly important for many developing countries. For a long time now the issue from a development policy point of view has no longer been around how to increase the quantity of investment inflows. The quality of FDI and the contribution they make to environment-friendly and inclusive growth processes is just as important. This is accompanied by a desire on the part of many developing countries to more strongly regulate their investment inflows in order to increase their positive effects on development. This shift in focus is not just a consequence of the disillusionment that many developing countries have experienced given the minor economic benefits stemming from the liberalization of their investment regimes in the 1980s and 1990s. It is also a result of the economic success of emerging countries which frequently do not implement these recommendations for liberalization one-on-one. Furthermore the coherence of investment agreements also has to play a greater role in light of new systemic risks such as global finance and climate risks and increased interlinking between different areas of policy. Against this backdrop, the role and substance of international investment agreements (IIA) have been subject to intense discussion in recent times. IIAs were traditionally negotiated as tools to protect from western companies' FDI in politically unstable developing countries. This one-sided focus for IIAs is no longer appropriate today: the global investment regime is in a period of change which calls the traditional North-South logic behind IIAs into question. It is no longer just North American, European and Japanese companies that invest abroad but also their Chinese, Brazilian and Indian competitors. The need for better consideration of public and private interests in IIAs is also growing in industrialized countries as a result of the increase in reciprocal investment flows. Against this background the European Union (EU) has implemented a far-reaching institutional reform of its Common Commercial Policy as a result of the Lisbon Treaty: negotiating European IIAs now falls under the overall competency of the EU and no longer just the Member States. This merging of trade and investment policy making at EU level provides new starting points for future IIAs to be drafted in a more development-friendly manner. Development policy actors should pay greater attention to this policy area in order to increase the potential for FDI to promote sustainable development processes. The formal options for pressing for greater coherence between investment and development policy have increased as a result of Lisbon. In order to use this room to manoeuvre more effectively developing countries need additional support to increase their negotiating capacities.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Handel und Investitionen